A facile approach towards fabrication of super hydrophobic surface from functionalized silica particles. (August 2016) - Awais, M.; Jalil, M.; Zulfiqar, U.; Husain, S.W.
Abstract: A facile and cost effective method for fabrication of super hydrophobic surface on a glass substrate is studied. The surface is fabricated from surface functionalized silica particles, synthesized by sol-gel process with the average size of 200±10nm. These particles were functionalized with stearic acid to induce hydrophobicity followed by coating on a glass substrate. After coating, substrate was dried to remove excess solvent. The drying temperature was optimized and its effect on contact angle of hydrophobic surface was studied. It was observed that surface exhibits higher contact angle with increased drying temperature till the decomposition temperature of Stearic acid. Silica particles were characterized by using Scanning electron microscopy (SEM), thermal analysis was performed with Thermo gravimetric analysis (TGA) while the coated surface was studied using SEM and Contact Angle (CA) measurement.